Lime Swallowtail, Chequered Swallowtail, Citrus Swallowtail Papilio demoleus Linnaeus (Insecta: Lipidoptera: Papilionidae) - Delano S. Lewis (EDIS)
EENY-444, a 5-page illustrated fact sheet by Delano S. Lewis, is part of the Featured Creatures collection. It describes this Old-World butterfly that is a potential pest to citrus industries in the region — its distribution, life cycle, hosts, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, January 2009.